A New Encryption Key Generator Design with True Random Bits - Etem, Taha; Kaya, Turgay (Springer Nature, 2024)
As the importance of data security increases day by day, the new encryption method developments are also becoming more complex. Although logical and operational operators increase data security by complicating the algorithm, it can sometimes create disadvantages. Therefore, encryption algorithms must be chosen very accurately; research in this area has also generally been shaped around this focus. In the field of cryptology, the most important parameter is the encryption key. Generating, distributing, and hiding this key is one of the most important problems. Random number generators in cryptography should meet some requirements. For this purpose, we realized a new true random number generator. ESC-50 sound dataset is selected as a seed for random number generator. Applied design is approved by NIST 800-22 test suite, Ent test, UACI, and NPCR tests. All of these successful test results showed that our design can be implemented in encryption system as a key generator. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Keywords: Ent test; NIST 800-22 test suite; NPCR; True random number generator; UACI